Relationship between job stress, thinking style and symptoms of post-traumatic stress disorder in mental health nurses - Wuyi Liu; Lin Sun; Xunbao Yin; Huan Zhao; Guohui Zhu; Bo Lian; Hongwei Sun (Frontiers Media S.A., 2022)
IntroductionMental health nurses are often exposed to stressful events which may lead to feeling of stress in their daily work, and this feeling has a profound impact on nurses' mental health.AimThis study aimed to evaluate the relationship between job stress, thinking style and symptoms of post-traumatic stress disorder (PTSD) of mental health nurses, and to explore the mechanism of job stress and thinking style on symptoms of PTSD.MethodThis cross-sectional study collected related data of 351 mental health nurses in China, and the data was analyzed by PROCESS macro for SPSS.ResultsThe results showed that 18.2% of mental health nurses had the symptoms of PTSD. Thinking style (monarchic thinking style, anarchic thinking style and external thinking style) played a moderating role in the predictive effects of job stress on the symptoms of PTSD.DiscussionThe research pointed out the relationship between job stress and symptom of PTSD, and clarified the critical role of thinking style among mental health nurses.Implications for practiceIt is recommended that organizations should enact effective policy and intervention programs to reduce job stress and PTSD symptoms of mental health nurses which may improve their mental health level.